CLASSROOM SPEAKING ACTIVITIES IN A CONVERSATION CLASS: A CASE STUDY OF ONE JUNIOR HIGH SCHOOL IN BANDUNG - AGNYOTO, Panji (2012)
The study attempts to investigate the process of classroom speaking activities in a case of conversation class and students' responses to those activities. The respondents were an English teacher and his students in one Junior High School. The study employs qualitative explanatory case study design. The data were obtained through lesson plans, classroom observations, and interviews, and were then analysed by theory of Thornbury (2005) of speaking activity and its function. It is found that there are four activities conducted; Show and Tell, Presentation, Drama, and Question and Answer in a class. The students' responses to the four activities used are relatively varied. Drama appears to be the most dominant activity. It promotes comfort dominantly, while Presentation does the least. It is noted that preparation, teacher's feedback, and meaningful context play significant role in speaking activities.